ANALISIS KEMAMPUAN BERWIRAUSAHA PADA MAHASISWA/I PROGRAM STUDI MANAJEMEN FAKULTAS EKONOMI DAN BISNIS DI UNIVERSITAS NIAS RAYA - Wau, Yohana Melika (Jurnal Ilmiah Mahasiswa Nias Selatan, 2024)
The scope of this research is an analitycal study of entrepreneurial abilities in students of the Management Study Program Faculty of Economics and Business at Nias Raya University. The aim of this research is to determine and analysis the entrepreneurial abilities of students from the Management Study Program Faculty of Economics and Business at Nias Raya University. This research is descriptive qualitative research. The data collection techniques used are interviews, observation and documentation with data analysis, data reduction, data analysis and drawing conclusions. Based on the research results, the courage of students does not have entrepreneurial skills. The results of the reaserch show that before becoming an entrepreneur it is important to have entrepreneurial skills that can be a factor in the success or failure of a business.